Experimental studies method of controlled gravitational leakage of grain materials from physical model of dump hopper - Shymko, L. S. (НУБіП України, 2018)
In the article, for the purpose substantiate the parameters and operating modes of the harvester`s unloading devices, the method of experimental studies of controlled gravitational leakage from the dump hopper and its physical model is proposed. The peculiarity of the program for the study of free-flowing material`s leakage involves three stages, which include a joint common goal, individual experiments, the execution of which ensures the verification and, if necessary, the correction of the theoretical provisions, considerations and conclusions on improving the efficiency of the production process of harvesting grain crops. The research consisted of: the original experiment (the establishment of mechanical and technological properties of the working grain material of the main crops); modelling (construction and verification of the dump hopper`s physical model); the main experiment (studying the movement of grain from the dump hopper).
Методика експериментальних досліджень керованого гравітаційного витоку зернових матеріалів із фізичної моделі самоскидного бункера
У статті, з метою обґрунтування параметрів і режимів роботи вивантажувальних пристроїв збиральних машин, пропонується методика експериментальних досліджень керованого гравітаційного витоку із самоскидного накопичувального бункера збирального комбайна та його фізичної моделі. Особливість програм дослідження витоку сипких матеріалів передбачає три етапи, що включають в себе об’єднані спільною метою, окремі експерименти, виконання яких забезпечує перевірку та, при необхідності, корегування теоретичних положень, міркувань і висновків щодо підвищення ефективності виробничого процесу збирання зернових культур. Дослідження складалися із первинного експерименту – встановлення механіко-технологічних властивостей робочого зернового матеріалу основних культур; моделювання – побудова та перевірка фізичної моделі самоскидного бункера і основного експерименту – дослідження руху зерна із самоскидного бункера.
Keywords: grain harvester; tipper bunker; technique; experimental study; gravitational turn; grain materials; method; зернозбиральний комбайн; бункер; самоскид; техніка; експериментальні дослідження; гравітаційне поле; зерновий матеріал